1993
DOI: 10.1007/bf02294649
|View full text |Cite
|
Sign up to set email alerts
|

Local homogeneity in latent trait models. A characterization of the homogeneous monotone irt model

Abstract: stochastic subject, unidimensionality, local independence, experimental independence, local homogeneity, monotonicity, subpopulation invariance, pairwise determination, nonnegative association,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 11 publications
0
64
0
Order By: Relevance
“…It is attractive to use a model that is based on desirable measurement properties but does not impose the restrictions of a parametric family on the item response functions nor on the ability distribution. This paper will be based on NIRM that can be defined using the properties of monotonicity (M), conditional independence (CI), restricted or uni-dimensionality (RD/UD) (see, for example, Mokken, 1971, p. 77, p. 118; also Holland, 1981;Holland & Rosenbaum, 1986;Junker, 1993;Rosenbaum, 1984;Sijtsma & Molenaar, 1987), and marginal local homogeneity (MLH; Ellis & van den Wollenberg, 1993). Other NIRM with additional or different properties could be similarly treated.…”
Section: Nonparametric Item Response Modelsmentioning
confidence: 97%
“…It is attractive to use a model that is based on desirable measurement properties but does not impose the restrictions of a parametric family on the item response functions nor on the ability distribution. This paper will be based on NIRM that can be defined using the properties of monotonicity (M), conditional independence (CI), restricted or uni-dimensionality (RD/UD) (see, for example, Mokken, 1971, p. 77, p. 118; also Holland, 1981;Holland & Rosenbaum, 1986;Junker, 1993;Rosenbaum, 1984;Sijtsma & Molenaar, 1987), and marginal local homogeneity (MLH; Ellis & van den Wollenberg, 1993). Other NIRM with additional or different properties could be similarly treated.…”
Section: Nonparametric Item Response Modelsmentioning
confidence: 97%
“…Because of their generality, nonparametric models have proven to be excellent starting points for deriving properties of IRT models in general (e.g., Ellis & Van den Wollenberg, 1993;Hemker et al, 1997;Holland & Rosenbaum, 1986;Junker, 1991Junker, , 1993Stout, 2002). For example, Ellis and Van den Wollenberg (1993) showed that IRT models in general are true for subpopulations that have the same e but not for individual respondents.…”
Section: Fitting the Rasch Modelmentioning
confidence: 99%
“…For example, Ellis and Van den Wollenberg (1993) showed that IRT models in general are true for subpopulations that have the same e but not for individual respondents. This implies th at for a particular e value, say ed, a response probability like P(Xj = lied) = 0.7 (dichotomous scoring) means that 70% of the respondents having the same ed provide a 1 score and 30% a 0 score, whereas the same individual is assumed to provide the same item score across independent replications.…”
Section: Fitting the Rasch Modelmentioning
confidence: 99%
“…[It may be noted, by the way, that a distinction can be made between respondents and Os and, related to this, different definitions of the response probability; see Holland (1990) and Ellis and Van den Wollenberg (1993). We will ignore this distinction here for practical purposes.]…”
Section: Ordering Items Using the Item Meanmentioning
confidence: 99%